Entrepreneurial Potential of Urban and Peri-Urban Agri Enterprises: A Multidimensional Analysis - Suhana N; Smitha Baby (Archives of Current Research International, 2025)
Urban and peri-urban agriculture is rising as one of the major sectors in India, spurred by increasing urbanization, food security concerns, and entrepreneurial prospects. The study was conducted in this backdrop to assess the entrepreneurial potential of urban and peri-urban agri enterprises in the Central region of Kerala in terms of the multidimensions such as scaling readiness, profitability, product diversification strategy, marketing competence, employment generation, capacity utilization and ecological sustainability. Using Principal Component Analysis, the study identified two major components: strategic growth orientation (driven by marketing competence, employment generation, scaling readiness and product diversification strategy) and green innovation (highlighting ecological sustainability) as the pillars of entrepreneurship development in the urban and peri-urban scenarios. The study also highlighted that marketing competence as the most significant dimension while ecological sustainability had the least impact on the entrepreneurial potential. The Entrepreneurial Potential Index (EPI) analysis revealed that a majority of urban and peri-urban agri enterprises (66%) had a medium level of entrepreneurial potential. Also, significant differences in the entrepreneurial potential were observed among the three major categories of enterprises; with value-addition firms having the highest mean EPI, followed by mushroom enterprises and aquaponics with the lowest mean EPI, underscoring the prospects for development in these sectors. The study highlights the need for adopting strategies to enhance marketing competence of agri enterprises by focusing on branding, labelling, and packaging. Use of skilled employees, innovation readiness and multiple product development would also help to achieve a resilient and competitive urban agripreneurial ecosystem in the State.